Pengaruh Faktor Institusi dan Makroekonomi Terhadap Investasi Asing Langsung Pada Negara Berkembang Asia Tahun 2010-2024 - Betrand Nicholas Chandra; Nairobi; Rizka Malia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of institutional and macroeconomic factors, specifically Economic Freedom, Corruption Perceptions Index (CPI), political stability, economic growth, inflation, and lending interest rates, on Foreign Direct Investment (FDI) in ten developing Asian countries from 2010 to 2024. This research employs a quantitative approach using panel data regression with the Random Effect Model (REM) and robust standard errors to overcome autocorrelation. The results indicate that Economic Freedom, CPI, political stability, and economic growth have a positive and significant impact on FDI inflows. Conversely, inflation and lending interest rates do not significantly affect FDI. These findings suggest that institutional quality, such as market freedom, clean bureaucracy, and political security, alongside strong market capacity, are the primary determinants for multinational corporations when investing in developing Asia, rather than short-term monetary fluctuations.